ENGLISH HYDRONYMS AND THEIR STRUCTURE - Qurbonova Gulnoza Abduholiq qizi (American Journals, 2025)
This article explores the structure and origins of English hydronyms, which are names given to bodies of water such as rivers, lakes, and seas. It delves into the historical, linguistic, and geographical factors that have influenced the formation of these water names. By examining the influence of Celtic, Latin, Old English, Norse, and French, the article highlights how hydronyms reflect both the physical features of water bodies and the cultural significance attached to them. It also discusses the evolution of hydronyms over time, tracing their transformations through various periods of the English language, including Old English, Middle English, and Modern English. Key examples such as the River Thames, River Severn, and Lake Windermere are analyzed to showcase how names have been shaped by geographical features and historical events. The article emphasizes the importance of hydronyms in mapping human history, cultural interaction, and environmental connection, offering insights into the dynamic relationship between people and the landscape throughout the centuries.
Keywords: Hydronyms, English hydronyms, Linguistic evolution, Historical significance, River names, Water bodies, Toponymy, Celtic influence, Old English, Norse influence, Anglo-Saxon place names, Geographical features, Place names, Environmental interaction, Linguistic roots, Cultural influences, River Thames, River Severn, Lake Windermere, Hydronym structure, Old French, Latin influence.